The efficacy of Eprex drug preparation in prosthetic arthroplasty of large joints of the lower extremities - Kostrikova, Eleanora (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article represents results of a study of the efficacy of Eprex drug preparation in the patients, who underwent surgical interventions: hip and knee joint arthroplasty. The use of Eprex reduced the necessity to transfuse homological blood preparations in patients from the groups studied.